KEARIFAN LOKAL TRADISI SADRANAN KALI SEDANDANG DI TLAHAB TEMANGGUNG SEBAGAI BASIS NILAI-NILAI PENDIDIKAN KARAKTER - Naufal Raffi Arrazaq; Irvan Tasnur (Universitas PGRI Adi Buana Surabaya, 2023)
The study of the Sadranan Kali Sedandang tradition in Tlahab Temanggung as a source of learning local history and character education in the PPK movement in particular has not been carried out in depth by previous researchers. The purpose of the study is to analyze the history of Sadranan Kali Sedandang, the description of the implementation of Sadranan Kali Sedandang, and the values of character education based on local wisdom in the Sadranan Kali Sedandang tradition. The method used in this study is qualitative. The results showed that the history of Sadranan Kali Sedandang in general has a connection with the Shradda tradition that has existed since the time of the Majapahit Kingdom. Sadranan is also carried out as a form of the community's expression of gratitude for the ease of access to water and the abundance of crops. The tradition related to the expression of gratitude for the abundance of water is called Sadranan Kali Sedandang. The implementation of the Sadranan Kali Sedandang tradition begins with cleaning the environment, planting trees, praying together and Slametan. People bring various attributes such as offerings, tumpeng, ingkung from roosters, and market snacks. The Sadranan Kali tradition has the potential to be used as a source of learning local history and character education in the PPK movement.